Comparison of the collection of blood samples in prenatal screening, using the filter paper and venipuncture technique ELISA for the detection of syphilis - Gómez, Juan Fidel Bencomo; Appolinário, Marco A.O.; Castro, Antonio J.W. de; Martí, Jordi; Prates, Sidney; Santos, Cristimar dos; Oliveira, Áquila (Brazilian Journal of Sexually Transmitted Diseases, 2010)
Introduction: syphilis is a systemic disease of chronic evolution and caused by Treponema pallidum, a spirochete of sexual and vertical transmission, which can produce, respectively, the form of acquired and congenital disease. In Brazil, according to the Ministry of Health (MoH), although the underreporting of cases of congenital syphilis is high, some available data indicate the high magnitude of this problem that especially affects the weakness of pregnant women. Congenital syphilis causes great social impact, which results in deterioration of quality of life on a important stratum of the population, and indirect costs to the economy of the country, which, added to the direct costs resulting from hospitalizations and procedures for the treatment of its complications, increasing the total costs of care of public health. Objective: to compare the collection of blood samples on filter paper (FP) and plasma (gold standard) in prenatal screening, using anti-treponema total (IgG + IgM) in ELISA immunochemical. Methods: we studied 1,142 pregnant of the following cities: Itaboraí (N = 131), Itaguaí (N = 597), Niterói (N = 377) and St. João de Meriti (N = 37). Blood samples were collected from the finger and venipuncture of pregnant women in stations of collection of these counties, calculating elapsed time from sample collection to delivery of the report to the council. We calculated the limits of sensitivity, specificity, positive predictive value and negative for the study. Results: Itaboraí showed positive ELISA in 4.58%, in Itaguai, Niterói and St. João de Meriti showed, respectively, 3.18%, 2.65% and 0%. The procedures performed had a sensitivity and specificity of 100%, and the positive and negative predictive criteria for all pregnant women studied in 1,142 samples were 100%. All positive cases were reported to the Municipality within 10 days of sample collection. Conclusion: we conclude that the implementation of collection of dried blood on filter paper in pregnant women screening, was similar to that collected by venipuncture, validating this technology.